Method for testing water vapor transmittance of organic single crystal film

The preparation of organic single crystal thin films through physical gas phase transport method and combined with template peeling method and vacuum evaporation technology, the problem of difficult to measure the water oxygen barrier ability of organic single crystal materials is solved, and the accurate measurement of its water oxygen transmittance and devices are realized. Improved stability.

CN119269369AInactive Publication Date: 2025-01-07JILIN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411511721.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure and evaluate the water-oxygen barrier capacity of organic single crystal materials, especially because it is fragile and sensitive to organic solvents, and it is difficult to be applied to traditional calcium testing.

Method used

The organic single crystal thin film was prepared by physical gas phase transport method, and the calcium layer was placed under it through template peeling method and vacuum evaporation technology. The water vapor transmission rate was tested in combination with the calcium corrosion method, and the resistance change of the calcium electrode was used to calculate the water vapor transmission. Rate.

Benefits of technology

The accurate measurement of the water oxygen transmittance of organic single crystal materials is achieved, the current efficiency and working stability of the device are improved, and the excellent water oxygen barrier ability of organic single crystal materials is proved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269369A_ABST
    Figure CN119269369A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric devices, and particularly discloses a method for testing the water vapor transmittance of an organic single crystal film, which comprises the following steps: growing and preparing an organic single crystal, weighing organic single crystal material powder, placing in a double-temperature-zone quartz tube furnace, and preparing the organic single crystal film by using a physical vapor transport method as a core growth mechanism. Growing a flaky organic single crystal material on the inner wall of the quartz tube; the substrate is pretreated, the cleaned substrate is blow-dried through pure nitrogen, and the whole modifying and cleaning process is completed; the invention discloses a method for testing water vapor transmittance of organic single crystals. According to the method for testing the water vapor transmittance of the organic single crystal film, a large-area organic single crystal is prepared by using a physical vapor transport method, the Ca layer is arranged below the organic single crystal layer, and the Ca electrode is connected through the evaporated electrodes on the two sides, so that the water vapor transmittance of the organic single crystal film is tested. The organic single crystal material is subjected to water vapor permeation quantitative analysis by combining a template stripping method and a calcium corrosion method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optoelectronic devices, and in particular to a method for testing water vapor transmission rate of an organic single crystal thin film. Background Art

[0002] In recent years, mobile terminal technology has gradually become an indispensable tool in people's daily lives. As one of the new display technologies, organic light-emitting diodes (OLEDs), with their light weight, low power consumption, high contrast and bendability, have become a key technology for the development of high-performance and low-cost mobile terminals. However, in order to meet the requirements of commercial applications, OLED devices need to meet both high efficiency and long life. The organic materials used in the structure of OLED devices are very sensitive to water vapor and oxygen. They are easily oxidized and produce carbonyl compounds, thereby reducing the electroluminescent efficiency. At the same time, they will also react with water vapor to deliquesce and produce black spots, affecting the conductive properties and reducing the stability of the device. In response to this technical problem, the industry often combines a variety of packaging technologies (physical methods, chemical methods, and composite packaging methods) to isolate OLED devices from the environment to prevent the intrusion and penetration of water vapor and oxygen, so as to improve and extend the working stability and life of OLED devices. However, in order to ensure that the device has a longer service life, the water and oxygen barrier capacity of the general packaging film needs to reach 10 -6 g·m -2 ·d -1 In order to achieve this goal, higher requirements will be placed on the technical level of the packaging process, which will also greatly increase the production and manufacturing costs of OLED devices.

[0003] From the perspective of crystal morphology, organic semiconductor materials can be divided into two forms: crystalline and amorphous. The crystalline state includes single crystal and polycrystalline. Limited by the traditional OLED device preparation process, the thin films in OLED devices are mostly amorphous. The molecules in amorphous films are disordered, with high impurities and defects. They are easy to react with oxygen and water vapor in the air, causing oxidation and degradation of the materials, seriously affecting the working stability and life of the device. Compared with amorphous materials, organic single crystal materials have regular molecular arrangement, low impurities and defects, and tightly stacked molecules in the crystal. The molecules are subject to strong intermolecular forces due to π-π interactions, which will effectively block the intrusion and penetration of water vapor and oxygen. It has an ideal water and oxygen barrier capacity, and can obtain chemical stability and thermal stability far higher than amorphous materials. This provides a new idea for realizing highly stable and long-life OLED devices.

[0004] Check the material's ability to block water vapor and oxygen. Water vapor transmission rate is usually used to indicate the material's ability to block water and oxygen. Water vapor transmission rate (WVTR) is the main parameter for measuring and evaluating the water and oxygen barrier performance of materials. The high-precision WVTR test method is the basis for studying the water and oxygen barrier capacity of organic single crystals. At present, the commonly used methods for testing water and oxygen barrier capacity include the calcium method, coulomb method, and heavy water method. Among them, the calcium method test is widely popularized and applied due to its high precision. This method uses the characteristics of calcium as an active metal. It is very sensitive to water and oxygen and is easily oxidized after contact with air. Calcium reacts with H in the air. 2 O and O 2 After chemical reaction, Ca(OH) is generated 2 Compared with CaO, its conductivity is much lower than that of metal Ca. The resistance value of the test will change with the degree of calcium corrosion, and then the water and oxygen barrier capacity of the material will be evaluated. However, due to the properties of organic single crystal thin film materials such as being fragile, flexible and sensitive to organic solvents, it is difficult to process and prepare, and is not suitable for traditional calcium method testing. How to accurately measure and evaluate the water and oxygen barrier capacity of organic single crystals is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for testing the water vapor permeability of an organic single crystal film. A large-area organic single crystal is prepared by a physical vapor transport method, and then a Ca layer is placed under the organic single crystal layer by combining a template stripping method and a vacuum evaporation film, and the Ca electrode is connected through electrodes evaporated on both sides. The water vapor permeability of the organic single crystal material is quantitatively analyzed by combining the template stripping method and the calcium corrosion method, and the water vapor permeability of various organic single crystal materials is measured.

[0006] To achieve the above object, the present invention provides a method for testing the water vapor transmission rate of an organic single crystal thin film, comprising the following steps:

[0007] S1. Growth and preparation of organic single crystals: weigh 3 to 5 mg of organic single crystal material powder, place it in a dual-temperature zone quartz tube furnace, set the temperature of the sublimation zone and the crystallization zone respectively, and plan the growth time period of the single crystal. A constant flow rate of high-purity inert gas is introduced into the quartz tube furnace, and the physical vapor transport method is used as the core growth mechanism. The growth process lasts for 3 hours, and a thin sheet of organic single crystal material grows on the inner wall of the quartz tube;

[0008] S2, substrate pretreatment, placing the substrate that has been thoroughly cleaned with a cleaning agent in the center of a clean culture dish, using a pipette to accurately add a hydrophobic modifier to the center of the culture dish, and immediately covering the lid of the culture dish to seal it, placing the culture dish containing the hydrophobic modifier and the substrate in a vacuum oven, using the vacuum environment to promote the rapid volatilization of the hydrophobic modifier, and at the same time, this process effectively hydrophobizes the surface of the substrate. After the treatment is completed, the hydrophobically modified substrate is immersed in toluene, acetone, ethanol and deionized water in a predetermined order for ultrasonic cleaning, and each cleaning step is maintained for 10-30 minutes to ensure that the surface residues and impurities are completely removed, and the cleaned substrate is blown dry with pure nitrogen to complete the entire modification and cleaning process;

[0009] S3. A method for testing the water vapor transmission rate of an organic single crystal is to first pick the organic single crystal onto a substrate and then evaporate a Ca layer and an Ag layer through a patterned metal mask, and then test after transfer.

[0010] Preferably, in step S1, the temperature of the sublimation zone and the temperature of the crystallization zone in the dual-temperature zone quartz tube furnace are 270-380°C and 240-340°C respectively, the growth time is 2-3 hours, the inert gas is argon, and the flow rate is 30-40 mL / min.

[0011] Preferably, in step S1, the organic single crystal material is 1,4-bis(4-methylphenylvinyl)benzene or 2,6-diphenylanthracene.

[0012] Preferably, in step S2, the substrate is a single-sided polished Si substrate with a size of 1.4 cm×1.6 cm; the cleaning agent is acetone, ethanol and isopropanol, the hydrophobic modifier is octadecyltrichlorosilane, the amount is 10-30 μL, the modification temperature is 60°C, the time is 4 hours, and the vacuum degree of the vacuum oven is 0.1 MPa.

[0013] Preferably, the specific operations of step S3 are:

[0014] First, the thin sheet organic single crystal material grown in step S1 is transferred to the substrate pre-treated with hydrophobicity in step S2 using tweezers; an organic layer mask is covered on the substrate with the organic single crystal attached, and for the calcium corrosion electrical test, the metal Ca film is encapsulated using the organic single crystal material.

[0015] Preferably, the encapsulation operation is:

[0016] The organic single crystal material is transferred to the pretreated substrate, and then an 80nm Ag extraction electrode and a 100nm Ca electrode are deposited on the organic single crystal material by mask evaporation. The size of the calcium electrode is 0.5mm long and 1mm wide. Then, the device is transferred to the glass substrate as a whole using NOA63 photoresist. By measuring the resistance change of the metal Ca film, the content of water vapor penetrating the organic single crystal material is calculated, thereby determining the water vapor transmittance of the organic single crystal material. The calculation formula is as follows:

[0017] WVTR=-n·M(H 2 O) / M(Ca)·δ Ca ·ρ Ca ·L / a·d(1 / R) / dt;

[0018] Where n represents H 2 The reaction ratio of O and Ca, M(H 2 O) and M(Ca) represent H 2 Molar mass of O and Ca, δ Ca is the density of Ca, ρ Ca represents the resistivity of Ca, L and a represent the length and width of the metal Ca film respectively, and R is the resistance of the metal Ca film.

[0019] Preferably, the Ca electrode thickness is 80 nm and the evaporation rate is The thickness of the Ag electrode is 200 nm and the evaporation rate is

[0020] The advantages and beneficial effects of the method for testing the water vapor transmission rate of the organic single crystal film used in the present invention are:

[0021] Organic single crystal material is a material with water vapor barrier ability. The water vapor permeability of the encapsulated film is calculated by measuring the remaining thickness of the calcium film at more times. Organic single crystal is a sheet material, and it is difficult to prepare calcium corrosion test devices. Through the improvement of the template stripping method, devices for measuring calcium corrosion can be made. Using organic single crystals with high carrier mobility as water and oxygen barrier layer can improve the current efficiency and working stability of the device.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides a preparation process of a calcium corrosion device for measuring water and oxygen permeability of an organic single crystal;

[0024] Figure 2 The horizontal direction of the preparation flow chart of the calcium corrosion device for measuring the water and oxygen permeability of an organic single crystal according to the present invention;

[0025] Figure 3 The resistivity variation over time of the calcium corrosion device based on BSB-Me organic single crystal tested in the present invention;

[0026] Figure 4 The resistivity variation over time of the calcium corrosion device based on DPA organic single crystal tested in the present invention;

[0027] Figure 5 The organic single crystal optoelectronic device encapsulated by the organic single crystal thin film of the present invention and the device structure using the traditional material NPB as the device transmission layer, wherein (a) is the organic single crystal optoelectronic device encapsulated by the organic single crystal thin film of the present invention, and (b) is the device structure using NPB as the device transmission layer;

[0028] Figure 6 The brightness of the organic single crystal optoelectronic device encapsulated by the organic single crystal thin film of the present invention and the device using the traditional material NPB as the device transmission layer changes with time during continuous operation. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0031] The present invention grows sheet-like organic single crystal 1,4-bis(4-methylphenylvinyl)benzene (BSB-Me) or 2,6-diphenylanthracene (DPA), uses it as a water vapor barrier layer of a calcium corrosion device, tests the water and oxygen permeability, obtains the change of the device resistivity over time, and verifies the water vapor barrier effect of the organic single crystal.

[0032] Example 1

[0033] (1) Growth and preparation of BSB-Me organic single crystals:

[0034] 1. Material preparation:

[0035] Use a medicine spoon to measure 3 mg of BSB-Me powder material. Place the 3 mg powder in the high-temperature sublimation area of ​​the dual-temperature quartz tube furnace to ensure that the powder is evenly spread without accumulation.

[0036] 2. Temperature setting:

[0037] The temperature setting of the quartz tube furnace was adjusted to set the temperature of the high-temperature sublimation zone to 270°C and the low-temperature crystallization zone to 240°C. Such a temperature gradient is conducive to the sublimation and recrystallization process of the BSB-Me material.

[0038] 3. Gas circulation:

[0039] Argon (Ar) is introduced into the furnace at a stable flow rate as a carrier gas. The stable flow of argon can ensure the smooth migration of substances during the sublimation process and prevent interference from other impurity gases.

[0040] 4. Growth process:

[0041] Start the heating program, let the temperature in the furnace gradually rise to the set value, and keep it at a constant temperature. Set the growth time to 2.5h to ensure that BSB-Me has enough time to complete the recrystallization process in the low temperature zone.

[0042] (2) Preparation of hydrophobic Si substrate

[0043] 1. Cleaning process:

[0044] A single-side polished Si substrate with a size of 1.4 cm × 1.6 cm was selected.

[0045] The Si substrate was ultrasonically cleaned with acetone, ethanol, and deionized water in sequence, and each cleaning lasted for 30 minutes to thoroughly remove impurities such as oil, dust, etc. on the surface. After cleaning, the Si substrate was placed in an oven to dry to remove residual moisture.

[0046] 2. OTS hydrophobic treatment:

[0047] Place the dried Si substrate in a clean culture dish.

[0048] Use a pipette to measure 30 μL of octadecyltrichlorosilane (OTS) solution and drop it on the blank area of ​​the culture dish to avoid direct contact with the Si substrate surface. Quickly cover and seal the culture dish to prevent OTS from evaporating too quickly.

[0049] 3. Vacuum oven treatment:

[0050] Place the culture dish containing the Si substrate and OTS in a vacuum oven and adjust the vacuum degree to 0.1 MPa. Set the oven temperature to 60°C, turn on the heating and vacuum pump, and perform a vacuum drying process for 4 hours. During this process, OTS will form a hydrophobic film on the surface of the Si substrate.

[0051] 4. Post-processing and drying:

[0052] After vacuum drying, the Si substrate was taken out and ultrasonically cleaned again with toluene, acetone, ethanol, and deionized water for 30 minutes each time to remove unattached or incompletely reacted OTS and other impurities. Finally, the surface of the Si substrate was blown dry with nitrogen for standby use. At this point, the preparation of the hydrophobic Si substrate was completed.

[0053] Example 2

[0054] The difference from Example 1 is that 3 mg of DPA powder material is measured with a medicine spoon, the temperature of the high-temperature sublimation zone is set to 380° C., and the temperature of the low-temperature crystallization zone is set to 340° C. The rest of the contents are the same as Example 1.

[0055] Example 3

[0056] The test method of water vapor transmission rate of organic single crystal film is as follows:

[0057] (1) Preparation and characterization of BSB-Me and DPA organic crystal calcium corrosion devices:

[0058] The organic single crystal grown in Example 1-2 was transferred to a hydrophobic Si substrate; a mask was placed on the Si substrate and placed in a vacuum coating apparatus, and the vacuum was reduced to 5×10 -4 Pa, Ca electrode was evaporated on the surface of organic single crystal with a thickness of 80nm and a deposition rate of Then, NOA63 photoresist was dripped on the surface of the organic single crystal, and a glass sheet was covered and pressed tightly. After the photoresist diffused to the edge of the entire silicon wafer, the entire device was exposed to ultraviolet light for 10 minutes to solidify the photoresist. The device was then peeled off from the substrate with a blade and transferred to a glass substrate. The device was then placed in a vacuum evaporator again, and a mask was covered to evaporate the Ag lead electrode with a thickness of 200nm. The deposition rates were controlled to be

[0059] In order to characterize the water vapor permeability of BSB-Me and DPA organic single crystals, Ca and H in air were measured at room temperature. 2 O and O 2 Chemical reaction occurs to generate Ca(OH) 2 and CaO compounds, the specific reaction process is as follows:

[0060] Ca+H 2 O→CaO+H 2

[0061] 2Ca+O 2 →2CaO

[0062] CaO+H 2 O→Ca(OH) 2

[0063] Ca(OH) generated by chemical reaction 2 The conductivity of CaO is significantly lower than that of Ca, and the resistance of Ca will change with the degree of calcium corrosion. At the same time, 95% of the change in the resistance of the Ca film is caused by H 2 O penetration caused by 2The reaction is less (<5%), so only the water vapor transmission rate is considered during the test. By measuring the resistance change of the metal Ca film, the content of water vapor that permeates the barrier layer can be calculated, thereby determining the water vapor transmission rate of the barrier film. The calculation formula is as follows:

[0064] WVTR=-n·M(H 2 O) / M(Ca)·δ Ca ·ρ Ca ·L / a·d(1 / R) / dt; (1)

[0065] Where n represents H 2 The reaction ratio of O and Ca is 2; M(H 2 O) and M(Ca) represent H 2 The molar masses of O and Ca are 18 g / mol and 40 g / mol, respectively; δ Ca is the density of Ca, which is 1.55 g / cm 3 ρ Ca represents the resistivity of Ca, and its value is 3.91Ω·m; L and a represent the length and width of the metal Ca film, which are 0.5mm and 1mm respectively; R is the resistance of the metal Ca film.

[0066] (2) Preparation of OLED devices based on BSB-Me and DPA organic single crystal functional layers:

[0067] The organic single crystal grown in Example 1-2 was transferred to a hydrophobic Si substrate pretreated with hydrophobicity; the substrate was placed in a vacuum coating apparatus after being covered with an organic mask plate, and the vacuum degree reached 5×10 -4 After Pa, the light-emitting layer and the electron transport layer were sequentially deposited, which were 5% by mass of 4,4'-bis(N-carbazole)-1,1'-biphenyl (CBP) doped with acetylacetonate di(2-phenylbenzothiazole-C2,N)iridium(III) (Ir(bt) 2 (acac)) film (5%wtCBP:Ir(bt) 2 (acac)) and BPhen, with thicknesses of 20 nm and 40 nm, respectively, and deposition rates of and Then, the cathode mask was replaced and the Ca / Ag composite electrode was evaporated to a thickness of 3 nm and 80 nm, respectively, at deposition rates of and Next, NOA63 photoresist was dripped onto the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 15 minutes to cure the photoresist. The device was then peeled off from the substrate with a blade and transferred to a glass substrate. The device was then placed in a vacuum evaporator again, covered with an anode mask, and MoO 3 and Au, with thicknesses of 5nm and 12nm respectively, and the controlled deposition rates are and The structural diagram of the entire device is shown in Figure 5 As shown in (a). Figure 5 (b) is a device structure using the traditional material NPB as the device transport layer, which belongs to the prior art. The preparation of the top-emitting organic single crystal charge transport layer OLED device is completed, and then tested.

[0068] pass Figure 1 and Figure 2 The process shown can be used to prepare single crystal calcium corrosion devices. Figure 3 as well as Figure 4 It can be seen that after 24,000 minutes of water vapor corrosion, the resistivity of the BSB-Me single crystal calcium corrosion device can be maintained at 40% of the original resistivity, which proves the good water vapor barrier ability of the organic single crystal. After 24,000 minutes of water vapor corrosion, the DPA single crystal calcium corrosion device can still maintain 90% of the original resistivity, which shows that the DPA organic single crystal has better water vapor barrier ability. Figure 5 (a) and (b) respectively show an organic single crystal optoelectronic device encapsulated by an organic single crystal thin film and a device structure using traditional material NPB as the device transmission layer. Figure 6 The change in brightness over time of an organic single crystal optoelectronic device encapsulated by an organic single crystal thin film and a device using the traditional material NPB as the device transmission layer during continuous operation.

[0069] Therefore, the present invention adopts the above-mentioned testing method for the water vapor permeability of the organic single crystal film, and prepares a large area of ​​organic single crystals by using the physical vapor transport method. Then, by combining the template stripping method and the vacuum evaporation film, the Ca layer is placed under the organic single crystal layer, and the Ca electrode is connected through the electrodes evaporated on both sides. The water vapor permeability of the organic single crystal material is quantitatively analyzed by combining the template stripping method and the calcium corrosion method, and the water vapor permeability of various organic single crystal materials is measured.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for testing water vapor transmission rate of an organic single crystal thin film, characterized in that: The steps include: S1. Growth and preparation of organic single crystals: weigh 3 to 5 mg of organic single crystal material powder, place it in a dual-temperature zone quartz tube furnace, set the temperature of the sublimation zone and the crystallization zone respectively, and plan the growth time period of the single crystal. A constant flow rate of high-purity inert gas is introduced into the quartz tube furnace, and the physical vapor transport method is used as the core growth mechanism. The growth process lasts for 3 hours, and a thin sheet of organic single crystal material grows on the inner wall of the quartz tube; S2, substrate pretreatment, placing the substrate that has been thoroughly cleaned with a cleaning agent in the center of a clean culture dish, using a pipette to accurately add a hydrophobic modifier to the center of the culture dish, and immediately covering the lid of the culture dish to seal it, placing the culture dish containing the hydrophobic modifier and the substrate in a vacuum oven, using the vacuum environment to promote the rapid volatilization of the hydrophobic modifier, and at the same time, this process effectively hydrophobizes the surface of the substrate. After the treatment is completed, the hydrophobically modified substrate is immersed in toluene, acetone, ethanol and deionized water in a predetermined order for ultrasonic cleaning, and each cleaning step is maintained for 10-30 minutes to ensure that the surface residues and impurities are completely removed, and the cleaned substrate is blown dry with pure nitrogen to complete the entire modification and cleaning process; S3. A method for testing the water vapor transmission rate of an organic single crystal is to first pick the organic single crystal onto a substrate and then evaporate a Ca layer and an Ag layer through a patterned metal mask, and then test after transfer.

2. The method for testing water vapor transmission rate of an organic single crystal thin film according to claim 1, characterized in that: In step S1, the temperature of the sublimation zone and the temperature of the crystallization zone in the dual-temperature zone quartz tube furnace are 270-380° C. and 240-340° C. respectively, the growth time is 2-3 hours, the inert gas is argon, and the flow rate is 30-40 mL / min.

3. The method for testing water vapor transmission rate of an organic single crystal thin film according to claim 1, characterized in that: In step S1, the organic single crystal material is 1,4-bis(4-methylphenylvinyl)benzene or 2,6-diphenylanthracene.

4. The method for testing water vapor transmission rate of an organic single crystal thin film according to claim 1, characterized in that: In step S2, the substrate is a single-sided polished Si substrate with a size of 1.4 cm×1.6 cm; the cleaning agents are acetone, ethanol and isopropanol, the hydrophobic modifier is octadecyltrichlorosilane, the dosage is 10-30 μL, the modification temperature is 60°C, the time is 4 hours, and the vacuum degree of the vacuum oven is 0.1 MPa.

5. The method for testing water vapor transmission rate of an organic single crystal thin film according to claim 1, characterized in that: The specific operations of step S3 are: The thin sheet organic single crystal material grown in step S1 is transferred to the substrate pre-treated with hydrophobicity in step S2 by using tweezers; an organic layer mask is covered on the substrate with the organic single crystal attached, and for the calcium corrosion electrical test, the metal Ca film is encapsulated using the organic single crystal material.

6. The method for testing water vapor transmission rate of an organic single crystal thin film according to claim 5, characterized in that: The encapsulated operations are: The organic single crystal material is transferred to the pretreated substrate, and then an 80nm Ag extraction electrode and a 100nm Ca electrode are deposited on the organic single crystal material by mask evaporation. The size of the calcium electrode is 0.5mm long and 1mm wide. Then, the device is transferred to the glass substrate as a whole using NOA63 photoresist. The water and oxygen permeability of the organic single crystal material is measured by measuring the resistance change of the metal Ca film and using the calcium corrosion electrical test method. The content of water vapor that penetrates the organic single crystal material is calculated, thereby determining the water vapor permeability of the organic single crystal material. The calculation formula is as follows: WVTR=-n·M(H2O) / M(Ca)δCa·ρCaL / α·d(1 / R) / dt; Where n represents the reaction ratio of H2O and Ca, M(H2O) and M(Ca) represent the molar masses of H2O and Ca, respectively, δCa is the density of Ca, ρCa represents the resistivity of Ca, L and a represent the length and width of the metal Ca film, respectively, and R is the resistance of the metal Ca film.

7. The method for testing water vapor transmission rate of an organic single crystal thin film according to claim 6, characterized in that: The Ca electrode thickness is 80 nm and the evaporation rate is The thickness of the Ag electrode is 200 nm and the evaporation rate is

Citation Information

Patent Citations

  • Testing method for water vapor penetration rate of thin film

    CN107449704A

  • Method for testing water vapor transmittance of packaging film

    CN111458277A

  • Testing method for thin film encapsulation

    CN111781120A

  • OLED device based on organic semiconductor single-crystal charge transfer layer and preparation method thereof

    CN116075199A

  • Thin film bonded body

    JP2006290729A